Les Témoins de Jéhovah : un mouvement religieux aux caractéristiques d’un mouvement social - Christophe Zamord (Études Caribéennes)
This article observes that Jehovah’s Witnesses share similarities with a social movement. The writer uses the descriptions that sociologists such as Alain Touraine and Herbert Blumer give of social movements. The author of this article then goes on to show that those characteristics can be found in the Watchtower Society. He then concludes that the Jehovah’s Witness movement can be considered as a social movement due to its characteristics.